Choice in a variable environment: visit patterns in the dynamics of choice. - Baum, William M (2004)
Molar and molecular views of behavior imply different approaches to data analysis. The molecular view privileges moment-to-moment analyses, whereas the molar view supports analysis of more and less extended activities. In concurrent performance, the molar view supports study of both extended patterns of choice and more local patterns of visiting the choice alternatives. Analysis of the present data illustrated the usefulness of investigating order at various levels of extendedness. Seven different reinforcer ratios were presented within each session, without cues to identify them, and pigeons pecked at two response keys that delivered food on variable-interval schedules. Choice changed rapidly within components as reinforcers were delivered and, following each reinforcer, shifted toward the alternative that produced it. If several reinforcers were delivered consecutively by one alternative, choice favored that alternative, but shifted more slowly with each new reinforcer. A discontinuation of such a series of reinforcers by the delivery of a reinforcer by the other alternative resulted in a large shift of choice toward that alternative. These effects were illuminated by analysis of visits to the two alternatives. Changes in visit length occurred primarily in the first postreinforcer visit to the repeatedly reinforced alternative. All other visits tended to be brief and equal. Performance showed multiple signs of moving in the direction of a fix-and-sample pattern that characterized steady-state performance in earlier experiments with many sessions of maintaining each schedule pair. The analyses of extended and local patterns illustrate the flexibility of a molar view of behavior.